An examination of the extent and relationship between governance and financial disclosures by public higher education institutions in South Africa - Ambe, Q. N. (ACTA UNIVERSITATIS DANUBIUS, 2018)
Greater proportion of Public Higher Education Institutions (PHEIs) income is derived from government; therefore, public accountability is of immense importance. Conversely, prior literature is inconclusive on the efficiency and effectiveness of PHEIs public accountability systems. This paper examines the extent of and relationship between governance and financial disclosures by the South African PHEIs in terms of 2007, 2014 Department of Higher Education, and Training (DHET) Regulations for Reporting by PHEIs. Secondary data were collected for the period 2012 to 2016 employing exploratory research method using multiple case study in two phases. Firstly, qualitative data collection and analysis using content analysis of the DHET Regulations and 115 annual reports of 23 SA PHEIs. Phase two employed quantitative data analysis of the findings obtain from phase one. The results indicate moderately satisfied and satisfied levels of governance and financial disclosure respectively. It establishes a significant difference of and positive relationship between governance and financial disclosures by SA PHEIs. It recommends a Governance and Financial Disclosure Measurement Checklist, Rating Scale and Index to be used by Council, Management, and Stakeholders to measure the governance and financial disclosure level and DHET to ensure that submitted annual reports meet their requirements to ensure public accountability.
Article published in the ACTA UNIVERSITATIS DANUBIUS (Vol. 14, no. 6, pp. 7-23 )
Keywords: Public Accountability; Annual Report; Regulation for Reporting; State aid to education; Education--Finance